Spectator Games: A New Entertainment Modality For Networked Multiplayer Games - Drucker, Steven; He, Li-wei; Cohen, Michael; Wong, Curtis; Gupta, Anoop (Microsoft Research, 2003)
Networked multiplayer games are becoming tremendously popular. At any given moment on the Microsoft Game Zone (http://zone.msn.com), there are thousands of people playing Asheron’s Call or Age of Empires. Traditional board and card games are also increasingly being played online and will continue to gain in popularity. While networked games are certainly fun for active players, there is potentially a much larger audience: spectators. In most traditional games, such as football, the number of spectators far exceeds the number of players. The key idea presented in this paper is to tap this potential by making online games engaging and entertaining to non-players watching these games.